Mathematical formulas and scientific data : a quick reference guide - Kothandaraman, C. P. (Mercury Learning and Information, 2023)
Designed as a quick reference guide for engineers, mathematicians, scientists, and industry professionals, this book provides the essential formulas in all areas of mathematics and the key scientific data used in engineering and science. Part One covers the mathematical formulas from algebra, trigonometry, analytic geometry, differential and integral calculus, and vectors. Part Two covers MKS, CGS, and SI units, mechanical units, electrical and magnetic units, gases, elements, acoustics, materials, thermodynamics, radioactivity, geodetic data, astronomical data, optics, solids, organic and inorganic compounds, and more. Technical terms are defined, and theorems and applicable laws are stated and explained in detail. This data book is essential for every scientist, engineering student, and practicing professional. FEATURES:Covers key reference data in numerous areas of science and engineeringIncludes mathematical formulas and tables from elementary to advanced topicsDefines and explains technical terms and their uses.
Keywords: Mathematics -- Formulae.; Engineering -- Statistical methods.; elektronické knihy; electronic books